THE ROLE OF UNIVERSITY IN PREPARING YOUNG PEOPLE FOR PROFESSIONAL DEVELOPMENT - Evgeny G. Ivashkin; Marina E. Bushueva (Высшее образование в России)
This article focuses on the creation of a modern program for professional development of the youth, which provides the continuous support of a student in his/her personal self-becoming, in determination of his/her future, including personal development and career advancement.The program is based on a competence approach, considering vocational guidance and career development as components of a single complex. The purpose is to acquaint students with the economic and professional environment, enrich their perceptions of the professional world, form preparedness and ability to overcome difficulties on a basis of self-reflection. The program presupposes an active participation of adults – psychological and educational support of a student at school and university up to his/her integration into the world of work.